Closing the gap? Overcoming limitations in sociomaterial accounts of early literacy. (March 2020) - Burnett, Cathy; Merchant, Guy; Neumann, Michelle M
This article uses a sociomaterial perspective to explore how deficit views of young children's language and literacy are sustained and can be challenged. Foregrounding the notion of multiplicity, it considers how diverse sociomaterial relations work to uphold particular kinds of practice and particular arrangements of bodies and things over others. These relations may interfere with and interface with each other in different ways, sometimes sustaining but also potentially disrupting deficit discourses and practices. Our sociomaterial perspective is illustrated with a short vignette from a study of children and touchscreen tablets in an early years setting. An initial analysis is followed by a series of alternate and tentative tracings of other kinds of relations that play through those moments. The article contributes to debates about social inequality by troubling the certainties generated though deficit models of children's literacy, whilst working proactively to envision and produce alternate possibilities that foreground the potentialities generated as people and other materials assemble together.